How much farm succession is needed to ensure resilience of farming systems? - Christine Pitson; Jo Bijttebier; Franziska Appel; Alfons Balmann (EuroChoices, 2020)
Farm succession is a key policy concern of the EU's Common Agricultural Policy and the European Commission's proposals for the future. This article uses the agent-based model AgriPoliS to study the effects of the availability of potential successors in two agricultural regions, one in Belgium (Flanders) and one in eastern Germany (the Altmark). The analysis provides no indication that considerably fewer successors would threaten the ability of the farming systems to ensure an adequate provision of private and public goods. Most farm closures occur due to the low efficiency of some farms which hinders the ability of famers to cover true long-term opportunity costs, i.e. the possibility of earning a higher income outside agriculture. In both study regions, a lack of successors leads to adaptations which create new opportunities for other farms and, in Flanders, to higher economic prosperity at the regional level. The adaptations differ between regions due to existing farm structures, labour demands and costs, institutional frameworks, and the ability to exploit economies of scale. The results of the simulations challenge the notion central to many CAP policies – that more farm succession is better for European agriculture. These findings call for a contextualised reconsideration of agricultural policies which support structural change and regional growth – not hinder it.
Keywords: 330